A new Pd(II)‐supported catalyst on magnetic SBA‐15 for CC bond formation via the Heck and Hiyama cross‐coupling reactions. (6th November 2020) - Rahimi, Leila; Mansoori, Yagoub; Nuri, Ayat; Koohi‐Zargar, Behzad; Esquivel, Dolores
Abstract : Magnetic mesoporous silica composite (MNP@SiO2 ‐SBA) was obtained via embedding magnetite nanoparticles between SBA‐15 channels. It was silylated with N ‐(3‐(trimethoxysilyl)propyl)picolinamide (TMS‐PCA) and then complexed with Pd(II). The obtained supported Pd(II) catalyst (MNP@SiO2 ‐SBA‐PCA) was characterized by conventional methods. The prepared magnetic catalyst showed high activity in the Heck and Hiyama reactions under optimal reaction conditions, including solvent, amount of catalyst, base, and temperature. Aryl bromides and iodides showed better results than aryl chlorides, and the catalyst exhibited noticeable stability and reused several times. Abstract : The synthesis and characterization of TMSP‐PCA‐Pd(II) supported on magnetic SBA‐15 is reported. It is successfully used as an efficient magnetically retrievable catalyst for CC bond formation in Heck and Hiyama reactions.